Performance of a new flexible 19 G EUS needle in pancreatic solid lesions located in the head and uncinate process: A prospective multicenter study - Ginès, Angels; Fusaroli, Pietro; Sendino, Oriol; Seicean, Andrada; Gimeno-Garcia, Antonio Z.; Gratacós-Ginès, Jordi; Araujo, Isis K.; Rodríguez-Carunchio, Leonardo; Alós, Silvia; Lisotti, Andrea; Cominardi, Anna; Montenegro, Andrea; Fernández-Esparrach, Glòria (Endoscopy International Open, 2021)
Background and study aims The poor flexibility of large-bore EUS needles often leads to technical failure when sampling from the duodenum. The aim of this study was to evaluate the technical and diagnostic performances of a new Menghini tip 19G nitinol EUS needle for sampling pancreatic solid lesions in the head and uncinate process.Patients and methods This was a European prospective multicenter single-arm study. A maximum of four passes were allowed. In case of failure, different needles were permitted.Results We included 75 patients (51 % males) with lesions in the head (n = 68; 91 %) and uncinate process (n = 7; 9 %) (mean size: 33 ± 12 mm; number of passes: 1.8 ± 0.9). Technical success was seen in 71 of 75 (94.7 %). Diagnostic rates were 89.3 % (67/75) and 94.4 % (67/71) in the intention-to-treat (ITT) and per-protocol (PP) analysis, respectively. In the eight cases with failure, diagnosis was obtained with another needle (n = 4), from another lesion (n = 3) or with follow-up (n = 1). A histological sample was obtained in 64 patients (ITT 85.3 % and PP 90 %) and immunohistochemistry was successfully performed in 13 of 15 lesions in which it was required. No differences between rapid on-site evaluation (ROSE) and non-ROSE groups were observed regarding diagnostic success (87.5 % vs 91 %, P = 0.582) and diagnosis at the first pass (70 % vs 81 %, P = 0.289). Number of passes was lower in the ROSE group (1.4 + 0.9 vs 2.2 + 0.7, P < 0.001). One adverse event was recorded (1.3 %) consisting in a duodenal perforation after a single session EUS-ERCP. Conclusions The new nitinol Menghini tip 19G EUS needle showed high technical diagnostic success in safely sampling solid lesions in the head and uncinate process of the pancreas.